2019
DOI: 10.3390/app9081533
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nonlinear Thermal Radiation on MHD Nanofluid Thin Film Flow over a Horizontally Rotating Disk

Abstract: Nanoscience can be stated as a superlative way of changing the properties of a working fluid. Heat transmission features during the flow of nanofluids are an imperative rule from the industrial and technological point of view. This article presents a thin film flow of viscous nanofluids over a horizontal rotating disk. The impact of non-linear thermal radiation and a uniform magnetic field is emphasized in this work. The governing equations were transformed and solved by the homotopy analysis method and the ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…Kumam et al [32] probed the MHD Casson nanofluid flow. Shah et al [33] deliberated the flow of MHD thin film fluid with radiation impact. The MHD Casson nanofluid flow in a cylindrical tube was considered by Ali et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…Kumam et al [32] probed the MHD Casson nanofluid flow. Shah et al [33] deliberated the flow of MHD thin film fluid with radiation impact. The MHD Casson nanofluid flow in a cylindrical tube was considered by Ali et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the analytical solution of Equations to , we use HAM and the results obtained from HAM are compared with numerical results obtained by using the parallel shooting method. Many problems in mathematics are complex in nature and to find the exact solution is almost very difficult or even impossible.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of thermal radiations and Hall current is recently explored by Shah et al [41,42] for rotating surfaces. A detailed study on rotating surfaces with stretching sheet performed by Shah et al can be found in [43][44][45][46][47][48][49]. CuO containing nanofluid thin film flow inside a semi-annulus region is examined by Sheikholeslami and Bhatti [50] numerically with constant magnetic field.…”
Section: Introductionmentioning
confidence: 99%